Enriching sociocultural perspectives on the effects of idealized body norms: Integrating shame, positive body image, and self-compassion - Mills, Jennifer S.; Minister, Claire; Samson, Lindsay (Frontiers in Psychology, 2022)
Body image is an integral aspect of the psychology of the self. Idealized body images are ubiquitous in both traditional media forms (e.g., magazines, television) and social media (e.g., Facebook, Instagram). The sociocultural model of body image (i.e., the Tripartite Influence Model) emphasizes pathways between idealized body norms, appearance comparisons, internalization of body ideals, and body dissatisfaction and its outcomes. We summarize the model and identify some issues to be addressed in future work, particularly in light of the immense popularity of social media. We review three topics that are not included in the sociocultural model but that provide a more complete picture of the influence of societal body norms on body image: 1) body shame, 2) positive body image, and 3) self-compassion. Research on the nature, assessment, and relevance of these constructs is reviewed in detail. In terms of clinical applications of these areas of research for individuals at risk of body dissatisfaction, we suggest assessing for and targeting body shame, cultivating facets of positive body image, and teaching strategies for developing self-compassion.